Construction and Immunological Evaluation of Multivalent Hepatitis B Virus (HBV) Core Virus-Like Particles Carrying HBV and HCV Epitopes - Sominskaya, Irina (American Society for Microbiology (ASM), 2010)
A multivalent vaccine candidate against hepatitis B virus (HBV) and hepatitis C virus (HCV) infections was constructed on the basis of HBV core (HBc) virus-like particles (VLPs) as carriers. Chimeric VLPs that carried a virus-neutralizing HBV pre-S1 epitope corresponding to amino acids (aa) 20 to 47 in the major immunodominant region (MIR) and a highly conserved N-terminal HCV core epitope corresponding to aa 1 to 60 at the C terminus of the truncated HBcΔ protein (N-terminal aa 1 to 144 of full-length HBc) were produced in Escherichia coli cells and examined for their antigenicity and immunogenicity. The presence of two different foreign epitopes within the HBc molecule did not interfere with its VLP-forming ability, with the HBV pre-S1 epitope exposed on the surface and the HCV core epitope buried within the VLPs. After immunization of BALB/c mice, specific T-cell activation by both foreign epitopes and a high-titer antibody response against the pre-S1 epitope were found, whereas an antibody response against the HBc carrier was notably suppressed. Both inserted epitopes also induced a specific cytotoxic-T-lymphocyte (CTL) response, as shown by the gamma interferon (IFN-γ) production profile.